Farmers’ perception of on-farm conservation of cassava biodiversity in Ogun State, Nigeria - Akintunde, O. O. (2017)
Conservation of agrobiodiversity is a prerequisite for sustainable food production and this can be enhanced by improving farmers’ positive perception of it. This study examined farmers’ perceptions of the on-farm conservation of cassava biodiversity in Ogun State. Data collected from 160 cassava farming households using a multistage sampling procedure were analysed using descriptive statistics, weighted scores and means. Results show that the highest proportion of farmers (44.2%) strongly agree that the composition of cassava varieties has changed in the last five years owing to late maturity. Almost half of the farmers (49.3%) have abandoned local cassava varieties and “Gbego” cassava variety is the most abandoned variety. The perception of a typical farmer is that improved cassava varieties did not require more weeding than local ones but is undecided about fertilizer requirement and ease of harvesting. Improved cassava varieties are perceived to be bigger, early maturing, yield higher and are more disease resistant than the local ones. The farmers also perceive that improved varieties have more water content than local ones but was undecided on which had more tissue content. There is a close tie in the perception of the farmers about whether improved cassava tubers had higher market price, are more scarce to obtain or preferred to local varieties by processors than local varieties.